(untitled) (Proceedings of the International Conference on Education, 2019)
Sri Lanka introduced English as a medium of instruction in Public Schools country-wide in 2001 as a means of preparing the younger generation to face "Globalization" effectively. Such opportunities, though existed even before, had been limited to a few urban elite schools. Fifteen years of implementation of this policy needed a critical analysis. This paper reports an investigation of the challenges in implementation and expansion of English medium classes in schools. The research is based on a survey carried out with a sample consisting of English medium teachers and students. The study found that those who teach in English medium in urban schools are enthusiastic but majority of teachers, are not proficient enough in the language to teach in English. Comfortable and attractive classroom with up to date supporting technologies, effective training of teachers, and support by management of the schools will lead to better results. The students in English medium also needs support in improving language skills. They have an edge over others when pursuing higher education which is mostly in English medium. The paper concludes that the policy has been successful so far but it requires more focused resources if it is to expand successfully country-wide and provides some recommendations for way forward.